Yield Stability of Groundnut Cultivars in Ralstonia Wilt Endemic Areas in Indonesia: Yield Stability of Groundnut in Ralstonia Wilt Endemic Areas in Indonesia - Nugrahaeni, Novita; Purnomo, Joko; Rahayu, Muji; Janila, Pasupuleti (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
Bacterial wilt caused by Ralstonia solanacearum (Smith) is an important production constraint production of groundnut (Arachis hypogaea L.) in some countries of Asia including Indonesia. Seventeen wilt resistant lines, including 11 breeding lines, developed from the germplasm obtained from International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), five improved cultivars, and a susceptible check cultivar (i.e., MLGG 0627) were tested for their pod yield and stability of resistance to bacterial wilt in five bacterial wilt endemic areas in Indonesia. The plant wilt intensity across all locations was high on the susceptible check cultivar, indicating severe incidence of the disease. Among the improved cultivars, only Gajah exhibited resistance to the disease and its resistance was stable across locations, whereas the other five improved cultivars were susceptible to the disease. Eight out of the 11 breeding lines were highly resistant to this bacterial wilt, comparable or even higher than Gajah’s resistant level. All the resistant gentotypes produced average pod yield of 2.23 t ha–1, ranging from 1.01 to 3.28 t ha–1 , which was higher compared to pod yield of the susceptible lines. Only two breeding lines (i.e., ChiIc-8 and LPTr-12) exhibited high yield potential (i.e., >3.0 t ha−1). Average pod yield of susceptible genotypes ranged from 0.09 to 2.5 t ha–1 (mean, 0.87 t ha-1).